Interventional Programs for Genetically Disabled People Through Evidence-Based Advocacy - Oyamakin S. Oluwafemi; Dada Lawal (International Journal of Health Statistics, 2023)
Gene alterations that are essentially present in every cell in the body cause many hereditary diseases. As a result, these ailments frequently impact many bodily systems, and the majority of them are incurable. To treat or manage some of the accompanying symptoms, there might be methods available. When monitored up to the age of 25, it is estimated that 5.3% of babies will experience a genetic disease. In order to build a modified intervention program for people with genetic disorders, this paper reviewed existing programs and interventions for people with genetic disorders. It did this by using information about sickle cell disease. Data was gathered at the sickle cell clinic at the State Hospital, Adeoyo, Ibadan, Oyo state, where all sickle cell patients receive care. 53.3% of the survey participants were male (n=81), whereas 46.7% of the participants were female (n=71). In terms of age, 59.2% (n=90) of the respondents are under 20 years old, 27.6% (n=42) are between 21 and 26 years old, 9.9% (n=15) are between 26 and 30 years old, 1.3% (n=2) are between 31 and 35 years old, and 0.7% (n=1) of the respondents are each in the age brackets of 36 to 40, 41 to 45, and over 45. This demonstrates that the age range between 0 and 30 years old has the highest percentage of respondents, whereas people older than 30 are infrequently found. The respondents' marital status was also taken into account; 91.4% (n=139) of them are single, 7.2% (n=11) are married, and 1.3% (n=2) are separated.
Keywords: Genetics